PHYTOCHEMICAL SCREENING AND PHYTOCHEMICAL SCREENING AND PHYTOCHEMICAL SCREENING AND IN VITRO IN VITRO IN VITRO ANTIBACTERIAL ACTIVITY OF THE METHANOLIC LEAF EXTRACT: SEBASTIANIA CHAMAELEA MUELL. ARG - K. S. SHANTHI SREE; N. YASODAMMA; CH. PARAMAGEETHAM (The Bioscan, 2010)
Sebastiania chamaelea. a herbal medicinal plant belongs to the family Euphorbiaceae. Leaves contain a number of medicinally important phytochemical compounds. The preliminary phytochemical screening revealed the presence of 6 groups of secondary metabolites such as Phenols, Flavonoids, Tannins, Saponins, Steriods and Glycosides and qualitative analysis of Phenolic and Flavonoid compounds, resulted about 15 Phenolic compounds of which Caffeic acid, Melilotic acid, Aesculetin, P-Hydroxy benzoic acid, Coumarin, Cinnamic acid, Salicylic acid and Scopoletin have been identified along with 5, Flavonoid compounds like Myrecetin, Quercetin, Kaempferol, Luteolin and Apigenin. The antibacterial activity of the methanolic leaf extract of S.chamaelea against pathogenic bacteria like Bacillus subtilis and Staphylococcus aureus (gram positive) and Esherichia coli and Pseudomonas aruginosa (gram negative) bacteria showed concentration dependent inhibition of B. subtilis, S. aureus, P. aruginosa and E. coli.